IL6 shapes an inflammatory microenvironment and triggers the development of unique types of cancer in end-stage kidney - Peterfi, Lehel; Yusenko, Maria; Kovacs, Gyula (Anticancer research, 2019)
BACKGROUND/AIM: Chronic inflammation in end-stage kidney is associated with the development of pre-neoplastic lesions and renal cell tumors. The aim of this study was to clarify the role of the inflammatory microenvironment in this process. - MATERIALS AND METHODS: We used representative microscopic slides from 11 end stage-kidneys containing pre-neoplastic lesions and tumors and applied immunohistochemistry to detect IL-6, SAA1 and LBP expression. We also applied array-based comparative genomic hybridization (CGH) analysis to detect genomic changes in tumor cells. - RESULTS: We identified strong expression of IL6, LBP and SAA1 in activated stromal fibroblasts, in proliferating epithelial and tumor cells. Array CGH detected unusual genomic changes in tumor cells. - CONCLUSION: Our data indicate that expression of IL6, acute phase protein SAA1 and LBP maintain a long-lasting inflammatory microenvironment that leads to remodeling of end-stage kidneys and the development of unique types of renal cell tumors.
Gesehen am 06.06.2019